2008
DOI: 10.1002/cbf.1526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arachidonic acid and docosahexaenoic acid on differentiation and mineralization of MC3T3‐E1 osteoblast‐like cells

Abstract: Osteoblasts in culture can differentiate into mature mineralizing osteoblasts when stimulated with osteogenic agents. Clinical trials and in vivo animal studies suggest that specific polyunsaturated fatty acids (PUFAs) may benefit bone health. The aim of this study was to investigate whether arachidonic acid (AA) and docosahexaenoic acid (DHA) affect osteogenesis in osteoblasts and the transdifferentiation into adipocytes. Results from this study show that long-term exposure to AA inhibited alkaline phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 61 publications
1
15
1
Order By: Relevance
“…The final phase of osteoblast development is characterized by the formation of mineralized extracellular matrix. 29,30 Consequently, we propose that AA may play a role in accelerating the maturation of osteoblasts in the fracture healing event. We speculate that the speed of fracture healing may be enhanced by accelerating the maturation of osteoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…The final phase of osteoblast development is characterized by the formation of mineralized extracellular matrix. 29,30 Consequently, we propose that AA may play a role in accelerating the maturation of osteoblasts in the fracture healing event. We speculate that the speed of fracture healing may be enhanced by accelerating the maturation of osteoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…Lifestyle modifications, including exercise and dietary changes, can benefit bone and muscle. One such dietary attribute is the long chain n-3 PUFA, which has been studied in humans [74][75][76], animals [51,52,[77][78][79][80] and bone cell cultures [54,81] in order to understand their actions in bone metabolism and health. More recently, our laboratory [52,80] reported that DHA may be more beneficial to support bone formation and prevent bone loss, while other investigators [82,83] noted that low EPA levels were ineffective in maintaining bone mineral.…”
Section: Dietary Pufa Effects On Bone the Muscle And Bone Relationshmentioning
confidence: 99%
“…Expression of the CB2 receptor has been reported to be similar to ALP expression in this cell type [7]. There was no effect of PUFA on ALP activity using 10 μM treatments; studies that did show a PUFA effect used greater dosages [17] or for longer duration [18], which may act via the EC system and CB2 receptor, in particular.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the changes in substrates for EC synthesis may alter the expression of enzymes involved in the EC system. Based on the findings of Watkins et al [17] and others [18] that gene expression in and biomarkers elaborated by MC3T3-E1 cells are changed by exposure to different amounts and types of PUFA, the cellular EC signaling system likely adapts when exposed to these nutrients. Hence, investigating the adaptation to different dietary PUFA is important to understand the EC signaling pathways of cells, tissues and organs of the body.…”
Section: Introductionmentioning
confidence: 98%